The Dorsomedial Hypothalamus Is Involved in the Mediation of Autonomic and Neuroendocrine Responses to Restraint Stress - Brasil, Taíz F. S.; Lopes-Azevedo, Silvana; Belém-Filho, Ivaldo J. A.; Fortaleza, Eduardo A. T.; Antunes-Rodrigues, José; Corrêa, Fernando M. A. (Frontiers in Pharmacology, 2020)
We hypothesized that dorsomedial hypothalamus (DMH) modulates autonomic and neuroendocrine responses in rats at rest and when subjected to restraint stress (RS). Male Wistar rats were used, and guide cannulas were bilaterally implanted in the DMH for microinjection of vehicle or the nonspecific synaptic blocker CoCl2 (1mM /100nL). A polyethylene catheter was introduced into the femoral artery for the recording of cardiovascular parameters. Tail temperature was measured using a thermal camera. The session of RS started 10min after DMH treatment with vehicle or CoCl2. Under home-cage condition, the pretreatment of DMH with CoCl2 increased baseline blood pressure (BP), heart rate (HR), and tail temperature. In addition, it decreased plasma vasopressin levels without affecting plasma corticosterone and oxytocin contents. When rats were exposed to RS, the inhibition of DMH synaptic transmission by local pretreatment with CoCl2 did not affect the RS-evoked pressor and tachycardic responses but blocked the reduction in tail temperature caused by RS. In addition, DMH inhibition with CoCl2 did not modify the RS-evoked increase in plasma corticosterone and oxytocin contents. In conclusion, the present data suggest the involvement of DMH in the maintenance of blood pressure, heart rate, and vasopressin release under rest condition at the home-cage. Furthermore, indicate that DMH is an important thermoregulatory center during exposure to RS, regulating tail artery vasoconstriction.